Justiciability of the Common European Values : Enforcement of Article 2 TEU in Infringement Procedures - Lehtilä, Jasmin (My University, 2026)
The legal status of the Article 2 TEU, which lists the common European values on which the Union is to be founded, has had a solid basis in the foundational Treaties of the EU since the Treaty of Lisbon. It’s legal status and whether Member States’ obligations can be derived from the said Article has not, however, been clarified by the legislator or by the Court. The topic has been disputed by the academic community for several years, and now the Commission has answered to its critics by initiating an infringement procedure against Hungary, where it explicitly claims a violation of the values of Article 2 TEU. The claim was supported in the Opinion of the Advocate-General, but whether the pleanary of the Court is in accord remains to be seen. This thesis aims to explore how the values of Article 2 TEU could and should be used by the Court. The first part of the research is based on analysing whether the values may have direct justiciability, and it endeavors to explain why neither the procedural nor the material scope of the fundamental rights of the EU may be expanded by relying on obligations based on Article 2 TEU. As a result, the second part of the research focuses on indirect applicability of Article 2 TEU, and it explains how many of the said values, at least the ones claimed by the Commission in this case against Hungary, can be effectively enforced through other means of law. Lastly, the dispute surrounding the justiciability of Article 2 TEU is put to the relevant context by explaining the political discussion and pressures surrounding it. The main methods of this thesis are doctrinal legal research and law in context. In the end, this thesis takes a rather restrictive approach to the idea of using Article 2 TEU as a sole foundation of legal obligations for Member States. However, its importance is not denied in situations which clearly fall within the scope of EU law and respect the limitations the Court and the Treaties have traditionally assigned to human rights and other fundamental rights. Furthermore, it is argued that also less radical routes would be available for enforcing these important values; routes, which may not be as politically lucrative but, instead, maybe more sensible from the legal perspective.
Keywords: Article 2 TEU; Charter of Fundamental rights; Common European values; Fundamental Rights; Infringement procedure; Treaty on the European Union